Zjawisko amerykanizacji w języku i kulturze - Stępień, Ilona (Słowo. Studia językoznawcze, 2010)
The aim of this article is to show the impact of English on Polish culture and language. The influence of the United States of America on European and world countries is very strong, and was caused among other things by changes in means of communication between people and development of media, especially the Internet. The effects of this influence can be observed in various areas of life, e.g. advertising, business and computer science, where numerous borrowings appeared. We are also witnesses of adopting some American customs and traditions and copying certain elements of American lifestyle. In recent years also some changes in human relations occurred. One of them is simplification of verbal etiquette.